Students’ “Communication skill” Training Preferences at Dr. Rajendra Prasad Central Agricultural University, India - Sikdar, Samrat; Prakash, Satya (Indian Journal of Extension Education, 2025)
The study attempted to explore the preferences of the students enrolled in a Central Agricultural University of India (Dr. Rajendra Prasad Central Agricultural University) regarding future communication skills training programs from their placement point during 2024. Soft skills (especially the professional communication skills) have become one of the mandatory criteria for placement in contemporary India. It is quite insufficient to secure a job only based on the hard skills or knowledge as achieved throughout the degree program. This issue has received a tremendous attention by the different educational institutions in agriculture and allied sectors. 100 students from RPCAU were the respondents of this study, and they were asked to indicate their preferences regarding the future professional communication skills training sessions as conducted by the university’s placement cell. The students indicated their preferences regarding content, venue and duration of the future trainings, training participants’ size, time of the trainings, various methods used during those trainings, trainer types etc. The comprehensive view of the students’ preferences regarding the future soft skills trainings and this research study will be highly beneficial for the university administrators to sketch out the roadmap for future professional skills development trainings for the university students.
Keywords: Students; Communication skills; Training; Preferences; Placement.